Analysis of Movement of SASX - 30 Stock Exchange Index in Conditions of Slow Economic Growth - Alihodzic, Almir A. (Industrija, 2014)
Abstract: In the first quarter of 2012, almost all of the observed indexes in regional capital markets registered an increase in value, except for the capital market in BH, i.e. index of the Sarajevo Stock Exchange (SASX - 10) and Banja Luka Stock Exchange securities (BIRS). Therefore, the highest growth was achieved by the Serbian regional index (BELEX 15) in the amount of 6.59%, followed by Croatian (CROBEX) with 5.36%, Macedonian (MBI-10) with 2.56%, Montenegrin (MONEX) with an increase of 2.17% and Slovenian (SBI TOP) with the yield of 1.64 %. The largest decline in the value was registered by the Banja Luka index (BIRS) of 4.69 % and Sarajevo (SASX -10) for 3.57%. In this paper, we analyse the effect of four independent variables through multiple linear regression on a dependent variable. The dependent variable is the stock market index of the Sarajevo Stock Exchange (SASX - 30), while the independent variables in the model are the total turnover of shares, total loans of commercial banks, market capitalization and stock exchange index of the New York Stock Exchange (S&P 500). The main objective of this paper is to determine whether there is interdependence in the movement between the independent and dependent variables in order to better understand the factors that influence the movement of the SASX – 30 stock index. Key words: Stock Index, Turnover, Market Capitalizatio, S&P 500, Regression Analysis, Total Loans, The Global Financial Crisis